Bioactive potential of edel cocoa bean (theobroma cacao L) from Kedaton Jember: Cytotoxicity and antioxidants evaluation - Rina Sutjiati; Leliana S. Devi; Dwi Prijatmoko; Herniyati; Rudy Joealijanto; Erna Sulistyani; Bilqis P. Safitri; Nihla Fitriyani (Journal of Dentomaxillofacial Science, 2022)
Objective: Kedaton, a small village located in Jember is well known as one of the largest edel cocoa producers in the world. The cocoa beans contain nutrients and numerous beneficial properties, one of them is flavonoids, that work as antioxidants that can be utilized in dentistry, particularly orthodontics. The use of plants for the treatment must be ensured as safe without any toxic properties. Material and Methods: This study use DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) free radical method to evaluate antioxidant properties and MTT 3-(4.5-Dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide assay to assess the fibroblast cell activity. Results: The fermented edel cocoa bean extract exhibited the IC50 value of 33.97 ppm and the unfermented edel cocoa bean extract that had the IC50 value of 9.56 ppm. Both of them have very strong antioxidant activity. Fermented edel cocoa bean extract in concentrations of 1.56%, 3.125%, 6.25%, and 12.5%; as well as unfermented edel cocoa bean extract in concentrations of 1.56% and 3.125% did not have cytotoxic effects to fibroblasts. Conclusion: The unfermented edel cocoa bean extracts have higher antioxidant activity compared to fermented ones. The fermented edel cocoa bean extracts did not have cytotoxic effect, meanwhile the unfermented edel cocoa bean extracts in concentrations of 6.25% and 12.5% have cytotoxic effect to fibroblasts.